Strand 4: Issues in Developing the Networked Community: The Perspective of Members of Community Groups - Hammond, Michael (Proceedings of the International Conference on Networked Learning, 1998)
This paper explores some of the issues in developing networked communities. It begins with a background to some recent initiatives and is followed by a description of a short course on using the Internet which was offered co members of community groups in Sheffield. The paper describes and discusses aspects of the experiences of the course participants. Members of the course enjoyed taking part in on-line discussion but found constraints in contributing. They also enjoyed looking at WWW sites but found that their initial enthusiasm wore off. However course members did feel a sense of achievement in designing their own web pages – a process which was quite time consuming. I draw out four implications from this case study: Internet skills are relatively straight forward co acquire but not always easy to use in authentic context; access to discussion is the key to community networking even if there are significant constraints on taking part in on-line debate; virtual communities will not replace face to face meetings; national and international on-line networks of interest groups may develop more readily than those based on geographical proximity.